Theosophical elements in Iqbal's Magnum Opus "The Reconstruction of Religious Thought in Islam": a preliminary review - Hassan Mydin, Shaik Abdullah; Abdul Razak, Mohd. Abbas (2021)
Theosophy is a discourse on the divine wisdom of God behind all created things, which includes man who sits on the highest pedestal in the hierarchy of creations. Through this study, the researchers intend to analyze and discuss the theosophical elements found in Iqbal's thought process, particularly in his magnum opus "The Reconstruction of Religious Thought in Islam”. As a thinker, mystical poet and religious reformer, Iqbal’s ideas were anchored in the divine message of the Qur’an. The manifestation of his ideas in relation to theosophy in his work is not only interesting and unique, but at the same time they go in harmony with the positive demands of the modern world. The crux of his master piece focuses on subjects like nature, man and civilization in relation with God. Iqbal as a mystic has never failed to embed the element of spirituality to issues pertaining to the human survival that should go in tandem with the latest development in the area of modern science. Moreover, through his work, Iqbal emphasized that all philosophical thoughts that should be based on lofty spiritual values. For Iqbal, the human ego that originates from God, inherits some of God’s attributes like intelligence and creativity at a lesser degree. Man’s God given miniscule intelligence and creativity in no way can be equal to God’s attributes. A human being identified as an ego in Iqbal’s philosophy must recognize the position of God and subdue the forces around him/her in order to actualize his/her latent potentials. As a library research, the researchers will adopt the content and textual analysis methods in their effort to translate the relevant data taken from Iqbal's work. In addition, the researchers will refer to the Qur’an to validate as to whether Iqbal’s ideas are in line with the Tawhidic teachings of Islam.